Características e utilização das ferramentas de administração financeira na avaliação de empresas no Estado do Rio Grande do Sul: enfoque no risco x retorno - Wenzel, Ivan Liceu (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation verifies the current method sand procedures used to evaluate investments in companies located in the state of Rio Grande do Sul. Which investigate evaluation tools that are used, which yield earned and cherished over the capital and also that is measure das the variable risk. This is a descriptive research, analytical and exploratory, applied to two populations, one composed of the 100 largest companies in the state and another, of the 30 largest companies of the municipalities that had in 2009a GDP of more thanR$500 million. The objective is to check the state of Rio Grande do Sul managers of small and medium-sized companies use the same models for the financial evaluation that managers of large companies. The research was developed from a literature review on Investments and evaluation assessment models, Cost of capital and risk analysis. We carried out a statistical test of Kolmogorov-Smirnov test showed that the research sample is nonprobabilistic. With this result, we applied the Mann-Whitney test to compare means. For analysis and tabulation were done crosstab tables, histograms, by sector and often. Data were collected by sending electronic questionnaire previously elaborated. The research results show that there is a preference of financial managers to use as a primary end point the Accounting Rate of Return. Also, as a secondary criterion of evaluation are heterogeneous in their choices, the NPV is most used by the More while the Accounting Rate of Return is the choice of companies Minors. A possible conclusion was that little companies use the Payback method. Regarding the measurement of risk in the rate of return was found that most of the companies evaluated subjectively o rneither considers, contrary to the financial theory not to use quantitative methods to measure it. Also, regarding the propensity to risk, it is perceived that firms with managers with higher level of education have a higher debt than others. So, it is concluded that the value calculated by the investment analysis is influenced by the choices and way of how companies decide and act, also showing that managers are not exploiting to the full the techniques offered by financial theory, adapting them to their environment, in accordance with the requirement simposed by the market they serve.
Keywords: Risk; Profitability; Business evaluation; Risco; Rentabilidade; Avaliação de empresas; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis